ZIMDEF tenant management system - Musarira, Collen (Midlands State University, 2017)
ZIMDEF Tenant Management System is a computerized system that was developed with a purpose eliminating the problems faced by the organization when managing its tenants. The system allows ZIMDEF to advertise online the available space for rental to potential tenants. The interested tenants respond to the advert by applying for the space they want for their business purposes. The manager is responsible for accepting or rejecting the applications online. The accepted applicants are then automatically registered into the system. They will be notified via their email accounts that their applications were successful and the credentials that they will be using to access the system will also be attached in the email. The system calculates and sends the monthly bills to tenants’ accounts. The tenants should make their payments through ZIMDEF bank account and then upload the proof of payment on the system. The clerk is responsible for approving the proof payments uploaded by tenants. The research instruments that were used include interviews, questionnaires and observation. A comprehensive feasibility study of the system was weighed to enable evaluation of the practicability of the system and enabling determination of the system’s viability. This revealed that it was relevant to implement the new system. After the system was successfully designed, it was then tested in order to see if the user expectations were met. After system testing, the users were trained on how use the system. The system was installed on ZIMDEF servers and direct changeover strategy was used. There are various maintenance strategies to be used to make sure that the system continues to serve its purpose. The developer recommended that in future, the system must be integrated with other systems used by ZIMDEF so as to improve productivity. The system should also be made available on mobile devices to allow system users to access the system in remote places. The tools that were used to develop the system include PHP, MySQL, XAMPP and JavaScript. The system documentation was done using Microsoft word